18. Prevalence and factors the transmission of disease Transmissible Venereal Tumor (TVT) on dog hunter in Payakumbuh - Fadli Saputra; Roslizawaty Roslizawaty; Amiruddin Amiruddin; Nuzul Asmilia; T. Reza Ferasyi; Herrialfian Herrialfian (Universitas Syiah Kuala, 2017)
Tumor (TVT) aim of this study was to find out the prevalence and the factors were of Transmissible Venereal disease transmission on Dog Hunter in Payakumbuh. The study was conducted using a cross-sectional observational study (cross-sectional). Data collected through interviews by using questionnaires and observations of the condition of the Dog Hunter. The owners of hunter dogs were selected by purposive sampling. The obtained data were analyzed descriptively. Interviews were conducted with 110 people hunting dog owners with the total number of hunting dogs were observed as many as 300 individuals. The results showed that the prevalence rate of the Transmissible Venereal Tumor (TVT) disease on Dog Hunter in Payakumbuh is 1,33%. Factors the disease emergence were the mating habits of the dog were uncontrolled, the high levels of dogs sexual activity that was free to roam, the habitual of sniffing and licking genitals of infected dogs TVT, and also does not apply the principles of biosecurity property.